The Peningkatan Branding dan Manajerial Kelompok Usaha Agribisnis Oyster Mushroom Pada Bumdes Bedjo Djojo - dwiarko nugrohoseno; Witjaksono, Andre Dwijanto; Budiono, Budiono; Rozaq, Khoirur (Universitas Negeri Surabaya, 2024)
The results of the situation analysis show that the problems faced by partners are: First, the branding process for superior products such as product packaging, brands and designs that are less attractive. Some farmers have actually tried to package with good quality plastic. However, it is still lacking to make the product specific and have a positioning in the minds of consumers. Therefore, it is very important to make improvements in the product branding process so as to achieve competitive advantage. Second, the lack of knowledge and ability of business actors in online marketing to increase product sales. Third, as a relatively new business, oyster mushroom entrepreneurs have not yet done financial bookkeeping.Good business management must be supported by financial bookkeeping in an orderly and administrative manner. The solution to this problem is: First, efforts are needed to help oyster mushroom entrepreneurs in the form of training on packaging. Second, to further increase effectiveness and efficiency in product marketing in the current digital era, assistance needs to be provided in the form of training on online marketing. Third, training is needed on financial bookkeeping. It is hoped that assistance in the form of financial bookkeeping training, online marketing training and packaging improvements will be able to have a positive impact on improving and developing businesses for oyster mushroom business actors.